INTEGRATED ONE ROOF MANAGEMENT ADMINISTRATION SYSTEM IN PREVENTING AND MANAGING OF MOTORIZED VEHICLE LETTERS - Pambudi, Tegar Eris; Amarini, Indriati; Kartini, Ika Ariani (UMPurwokerto Law Review, 2020)
The falsification of motor vehicle papers is a form of crime that often occurs in the community. This study aims to analyze the administration of a one-stop motorized unified administrative system in preventing and overcoming the falsification of motorized vehicle documents and sanctions for falsifying documents. This research is normative juridical. The research approach is carried out through literature studies that examine secondary data in the form of books, journals, research results, and legislation. The results showed that the prevention and control of falsification of motorized vehicle documents were carried out by the Joint Office of the one-stop single administration system based on Presidential Regulation No. 5/2015 concerning the Implementation of the One-Stop One-Stop Administration System. The provisions of sanctions in the falsification of a letter are regulated in Articles 263-276 of the Criminal Code. The implementation of an integrated one-stop administration system between the Samsat Office and the police as law enforcement officers are needed to reduce the falsification of motorized vehicle documents. Keywords: SAMSAT, Letter Counterfeiting, Motorized Vehicles